Observing the mass balance and emergence velocity of a temperate glacier on Mt. Yulong, southeastern Tibetan Plateau - Yan, Xingguo; Wang, Shijin; Sun, Zhenqi; Ma, Xinggang; Pu, Tao; He, Yuanqing (Earth surface processes and landforms, 2025)
Temperate glaciers in the southeastern Tibetan Plateau are shrinking rapidly in response to ongoing climate change. This study focuses on the Baishui River Glacier No. 1, a typical temperate glacier in the Yulong Snow Mountain. Through field observations over four years, we have obtained records and valuable data on the mass balance, ice flow velocity and emergence velocity. The results show that it has been in a state of negative mass balance in recent 4‐years. The mass loss ranges from 1.17 ± 0.18 to 1.46 ± 0.25 m w.e., with an average annual mass loss of 1.29 ± 0.17 m w.e. The average ice flow velocity is ~29.24 ± 3.51 m yr−1, with spatial differences related to glacier morphology and mass turnover. These differences can be attributed to the glacier's morphological characteristics (such as width, slope, thickness and crevasse) and the large mass turnover conditions. In its low‐latitude wet climate, BRG1 has a fast emergence velocity of ~4.07 ± 1.03 m yr−1. The emergent ice flow is insufficient cannot offset melting. Slope change uncertainties hamper calculating surface mass balance from emergence velocity. Our data reveals a significant correlation (r2 = 0.69) between ice flow velocity and emergence velocity, and a very significant negative one (r2 = 0.78) between ice flow velocity and mass balance. Faster ice flow transports more ice to lower, warmer areas, accelerating melting. The data presented in this article offers valuable and useful insights into the physical ice flow model of such low‐latitude temperate glaciers. At Baishui River Glacier No. 1 in Yulong Snow Mountain, even if the horizontal and vertical velocities are accurately measured, the large uncertainties related to the slope changes prevent us from calculating the point surface mass change from the emergence velocity.